Analisis Pengiriman Data dari LoRa Gateway ke Network Server - Rosyida Zain, Ayu; Hudi, Siti Azka Rahmawati; Neforawati, Indri (MULTINETICS, 2021)
The development of IoT in Indonesia encourages the development of networks that IoT devices need to be able to communicate between sensors and actuators. One of the networks that helps the communication process is LoRa. LoRa (Long Range) is a wide area network protocol with low power and resistant to interference from unwanted signals. LoRa has limitations, that is it cannot send data directly to the network server. So it requires a device that can bridge data transmission to the network server, it called LoRa Gateway. Because the use of LoRa Gateway is very important in this case, an analysis is carried out to see how much data is used and what protocol are used when the communication from the LoRa Gateway to the Network Server occurs. The method used is data collection, data processing, and data analysis. The conclusion of this analysis is that the Spreading Factors (SF) and the time interval used while sending data have an effect on the size of kilobytes and the speed of sending data to the network server